THE SYSTEMATIC REVIEW OF ADULTS AIRWAY DEVICES IN AWAKE TRACHEAL INTUBATION - Nurochman Sidik, Fajar; Muhammad Suharyo, Dhimas; Solehudin, Hipni; Lesmana Putri, Fitria (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Although flexible bronchoscopes are often used for awake tracheal intubation, other airway instruments including videolaryngoscopes, direct laryngoscopes, and optical stylets are becoming more and more useful. Aims : This systematic review is to review the the effects for airway devices on patients with awake tracheal intubation. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SCIENCE DIRECT, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 431 articles, whereas the results of our search on SCIENCE DIRECT brought up 289 articles. The results of the search conducted for the last year of 2014 yielded a total 23 articles for PubMed and 115 articles for SCIENCE DIRECT. In the end, we compiled a total of 6 papers, 5 of which came from PubMed and 1 of which came from SCIENCE DIRECT. We included six research that met the criteria. Conclusion: In summary, in the context of awake tracheal intubation, flexible bronchoscopes, optical stylets, and channelled and unchannelled videolaryngoscopes were clinically equivalent airway devices. The time to tracheal intubation was longest with flexible bronchoscopes and shortest with optical stylets.